2022
DOI: 10.1093/plankt/fbac066
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of the biogeographical distribution of Rotifera in Africa

Abstract: The rotifer fauna of Africa has been studied for >100 years, but there has been no recent synthesis. We compiled data from 265 publications that reported information on African rotifers. Our dataset yielded information on the distribution of 765 taxa from ~1850 separate sites; these included both natural and artificial habitats such as lakes, ponds, puddles, oases, artificial systems, rivers and wetlands. A heat map of predicted rotifer biodiversity indicated that the greatest diversity should be presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Our extensive screening of the published literature allowed us to report 957 taxa from the area and make the dataset freely available online through the Open Science Framework (OSF) and the Global Biodiversity Information Facility (GBIF). The number of known species from Africa increased from the 639 reported in the first review from 1986 (De Ridder, 1986) to the 765 in the most recent compilation in 2022 (Smolak et al, 2023). Segers (2008) reported 591 rotifer species (453 Monogononta, 138 Bdelloidea) from the Afrotropical biogeographic region, partially overlapping with the geographic scope of the current review.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our extensive screening of the published literature allowed us to report 957 taxa from the area and make the dataset freely available online through the Open Science Framework (OSF) and the Global Biodiversity Information Facility (GBIF). The number of known species from Africa increased from the 639 reported in the first review from 1986 (De Ridder, 1986) to the 765 in the most recent compilation in 2022 (Smolak et al, 2023). Segers (2008) reported 591 rotifer species (453 Monogononta, 138 Bdelloidea) from the Afrotropical biogeographic region, partially overlapping with the geographic scope of the current review.…”
Section: Introductionmentioning
confidence: 66%
“…The dataset includes 27,455 records of 957 valid taxa of rotifers: 39 at subspecies, 819 taxa at species, 1 at species group, 81 at genus, and 17 at family level. This detailed literature search increased the number of known rotifer taxa at species, subspecies, form and variety level reported in previous reviews, which were 639 in 1986 (De Ridder, 1986) and 765 in 2022 (Smolak et al, 2023). Of the taxa reported in the current dataset, 167 (18%) are Bdelloidea, 665 (69%) Ploima, 97 (10%) Flosculariaceae, 27 (3%) Collothecacea and one representative of Seisonacea, the marine epizoic rotifer Seison africanus Sørensen, Segers & Funch, 2005 described and recorded only from coastal waters of Kenya (Sørensen et al, 2005).…”
Section: Summary Statisticsmentioning
confidence: 97%
See 2 more Smart Citations
“…2). In detail, Musazzi et al (2023) report 4,124 records of sedimentary diatoms in Lake Maggiore, a wide (2023) in comparison to 765 that were reported in the most recent review on African rotifers (Smolak et al, 2023); 584 species are reported for Italy by Ferrari et al (2023) in comparison to 483 reported in the most recent review on Italian rotifers (Fontaneto et al, 2022).…”
mentioning
confidence: 88%